(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper describes deep learning algorithms for character recognition. The huge amount of data and algorithms now makes it easier to train detailed neural networks. Character recognition is another application running using otherapproaches. This paper provides a CNN (Convolutional Neural Network) -based character recognition method. Trainyour dataset and classify it to see the results.A character recognition system was designed using image segmentation. Character recognition is done by the help of the python programminglanguage